2022
DOI: 10.3390/ph15091040
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Inhibitor of the Human Cytomegalovirus Core Nuclear Egress Complex

Abstract: The replication of human cytomegalovirus (HCMV) involves a process termed nuclear egress, which enables translocation of newly formed viral capsids from the nucleus into the cytoplasm. The HCMV core nuclear egress complex (core NEC), a heterodimer of viral proteins pUL50 and pUL53, is therefore considered a promising target for new antiviral drugs. We have recently shown that a 29-mer peptide presenting an N-terminal alpha-helical hook-like segment of pUL53, through which pUL53 interacts with pUL50, binds to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The herpesviral nuclear egress complex (NEC) represents a functionally highly important determinant of viral replication efficiency. Recent studies on HCMV indicated that the disruption of the hook-into-groove interaction of pUL50 and pUL53 inhibits the late phase of viral replication [ 24 , 34 , 40 , 46 ]. Considering the features of core NEC sequences and structures, we addressed the question of whether distinct cysteine residues might be accessible to the attack of inhibitory warhead compounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The herpesviral nuclear egress complex (NEC) represents a functionally highly important determinant of viral replication efficiency. Recent studies on HCMV indicated that the disruption of the hook-into-groove interaction of pUL50 and pUL53 inhibits the late phase of viral replication [ 24 , 34 , 40 , 46 ]. Considering the features of core NEC sequences and structures, we addressed the question of whether distinct cysteine residues might be accessible to the attack of inhibitory warhead compounds.…”
Section: Resultsmentioning
confidence: 99%
“…As a methodological trait, however, it has to be emphasized that the speckled appearance of nuclear rim, i.e., the drug-mediated disruption of the typical NEC nuclear rim localization, does not allow the direct conclusion of a dissociation of the pUL50–pUL53 core NEC heterodimer/oligomer. Previous studies of our group demonstrated that the speckled appearance of the HCMV core NEC can be induced by both direct inhibitors of core NEC proteins and indirect inhibitors of NEC-associated proteins [ 24 , 25 , 34 , 40 ]. As an important finding of the present study, nonetheless, this novel group of warhead small molecules likewise exerts a pronounced phenotypic effect on the viral NEC nuclear rim localization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the interacting region of c-MYC for USP37 is structurally disordered, it may not be a suitable target for small molecule inhibitor and/or disruptor [ 55 ]; rather, a peptidyl disruptor could be used to block the interaction between USP37 and c-MYC. Peptidyl disruptors has shown effective inhibition for the protein complex formation such as human ACE2 and the receptor-binding domain (RBD) of the Spike protein of SARS-CoV2 [ 56 ] YAP/TAZ-TEAD Transcriptional Complex [ 57 ] and Human Cytomegalovirus Core Nuclear Egress Complex [ 58 ]. Nearly 80% of the residues of c-MYC that interacts with USP37 have been found interacting with the designed peptide, suggesting that the peptide is specific to c-MYC-USP37 complex and could be used for targeted therapy against the ABC subtype of DLBCL.…”
Section: Discussionmentioning
confidence: 99%